Maintaining professional integrity in Iranian nurses - Ali Asghar Jesmi; Khadijeh Yazdi; Zahra Sabzi (Medicinski glasnik, 2019)
Aim: To determine obstacles in maintaining professional integrity of nurses and their strategy to overcome them. Methods: A conventional content analysis was conducted by 16 interviews. The data collection instruments were semi-structured interviews, observation and field notes. The interviews were recorded and transcribed verbatim, then analysed by Grandhime and Landman approach. For the validity and reliability of the study Guba and Lincoln criteria were used. Results: Latent meanings were formulated into "passive management", "inefficient organization", and "solid spirituality" themes. Passive management consisted of "lack of support from managers", "not understanding the nurses" and "improper supervision system". Inefficient organization was composed of "nursing staff shortages", "underestimation of nurses' roles" and "high workload". "Religious beliefs" and "personal beliefs" constituted the "solid spirituality" theme. Conclusion: There are factors that decline motivations in Iranian nurses; nevertheless, it is still possible to be a professionally integrated nurse. Among many factors contributing to internalization of professional integrity of nurses, spirituality is one of the most prominent factors.
Keywords: Codes of Ethics; qualitative research; nurse; spirituality